Efficacy and Usability of a Novel Barrier Device for Preventing Injection Port Contamination: A Pilot Simulation Study. (March 2020) - Wax, David B.; Shah, Anjan; Shah, Ronak; Lin, Hung-Mo; Katz, Daniel
Abstract : Contamination of intravenous (IV) ports and stopcocks has been associated with postoperative infections. We tested the usability and efficacy of a novel passive shielding device to prevent such contamination even in the absence of hand hygiene or port disinfection. In a desktop setting with deliberately contaminated hands, qualitative port contamination was detected after 5/60 (8.3%; 95% confidence interval [CI], 2.8–18.4) control port injections versus 0/60 (0%; 95% CI, 0–6.0) shielded injections ( P = .025). In clinical simulations with a quantitative bioburden assay (measured in relative light units [RLUs]), median (interquartile range [IQR]) postsimulation bioburden was 46 (32–53) vs 27 (21–42) RLU for the control versus intervention groups ( P = .036), yielding a median shift of −13 RLU (95% CI, −2 to −26) in favor of the shielding. Usability of the device was acceptable to practitioners.